1989
DOI: 10.1159/000261170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eating Cheese on Ca and P Concentrations of Whole Mouth Saliva and Plaque

Abstract: A study was undertaken to examine the release of calcium and phosphate from cheese during mastication. Unstimulated saliva was collected for baseline analysis in the initial study followed by saliva collection after chewing different cheeses with and without biscuits. In the second study, volunteers who had abstained from toothcleaning for 24 h had plaque samples taken from two quadrants, they then chewed cheese in their own personal eating manner, and a second sample of plaque was taken within 5 min. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
6

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 12 publications
3
25
0
6
Order By: Relevance
“…2 However, this is probably accounted for by the weight of the cheese cube consumed, which in some studies has been as low as 5 g. 2 The baseline values obtained for plaque calcium concentration on the first visit made by the subjects (4.2 (1.1-7.4) µg/mg dry weight) are similar to those previously reported for students and for children aged 11 years (4.5 µg/mg and 3.8 µg/mg dry weight respectively) 18 and for children aged 11 to 14 years (5.5 µg/mg dry weight). 14 The range of baseline values obtained in the present study is narrower than previously reported 14 which may reflect the standardisation procedures employed (such as a period of abstinence from oral hygiene and period of fasting prior to each experiment).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 However, this is probably accounted for by the weight of the cheese cube consumed, which in some studies has been as low as 5 g. 2 The baseline values obtained for plaque calcium concentration on the first visit made by the subjects (4.2 (1.1-7.4) µg/mg dry weight) are similar to those previously reported for students and for children aged 11 years (4.5 µg/mg and 3.8 µg/mg dry weight respectively) 18 and for children aged 11 to 14 years (5.5 µg/mg dry weight). 14 The range of baseline values obtained in the present study is narrower than previously reported 14 which may reflect the standardisation procedures employed (such as a period of abstinence from oral hygiene and period of fasting prior to each experiment).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence have shown that consumption of a cube of cheese following carbohydrate foods may protect against dental caries, probably by increasing the plaque calcium concentration [1][2][3][4] and the pH of plaque. 1 However, cheese is not usually consumed alone following a meal and it is not known whether cheese, as it is habitually consumed, as part of a cooked mixed meal, is protective.…”
Section: Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies have shown that supplementation of a cariogenic diet with milk substantially reduced dental caries incidence (Reynolds &Johnson, 1981). Plaque pH studies have shown that milk causes only a negligible decrease in plaque pH (Jenkins & Ferguson, 1966;Rugg-Gunn et al 1985), enamel slab studies have shown that milk solids can reduce the cariogenic potential of sugar-containing foods (Thompson et al 1984), and Bowen et al (1991) have shown that milk does not produce dental caries even when given in a caries promoting environment.…”
Section: Other Protective Factorsmentioning
confidence: 99%